2022
DOI: 10.1007/s12152-022-09505-y
|View full text |Cite
|
Sign up to set email alerts
|

Societal Collapse and Intergenerational Disparities in Suffering

Abstract: The collapse of society is inevitable, even if it is in the distant future. When it collapses, it is likely to do so within the lifetimes of some people. These people will have matured in pre-collapse society, experience collapse, and then live the remainder of their lives in the post-collapse world. I argue that this group of people—the transitional generation—will be the worst off from societal collapse, far worse than subsequent generations. As the transitional generation, they will suffer disparately. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A broader spectrum of emotional responses to climate change was charted by Moser (2020), including climate grief, solastalgia (emotional distress related to climate change), climate anxiety, guilt, fear, and profound grappling with the meaning of what scientists are saying. In addition, Crutchfield (2022) concluded that people who will have matured in pre-collapse society, experience collapse, and then continue to live in the post-collapse world will suffer more and feel much worse than subsequent generations.…”
Section: Future Climate Change and Societal Collapsementioning
confidence: 99%
“…A broader spectrum of emotional responses to climate change was charted by Moser (2020), including climate grief, solastalgia (emotional distress related to climate change), climate anxiety, guilt, fear, and profound grappling with the meaning of what scientists are saying. In addition, Crutchfield (2022) concluded that people who will have matured in pre-collapse society, experience collapse, and then continue to live in the post-collapse world will suffer more and feel much worse than subsequent generations.…”
Section: Future Climate Change and Societal Collapsementioning
confidence: 99%